The impact of effective teaching strategy according to the role-playing and participatory method of learning some motor skills in football - Nuhad, Tariq Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The current research aimed to identify the effect of using an effective teaching strategy according to an educational program using a participatory method and a role-playing method to learn some football skills, and to identify an advantage in the effect of using an effective teaching strategy according to one of two methods in learning some football skills. The research problem touched on the failure to achieve the educational goals set for the curriculum through the units in the command method (followed) used to teach football skills, and this decrease may be due to the lack of time and the short term period or to the negativity of the student being a recipient only in addition to the density of the number of students per group during Practical lectures, which increases the burden of the educational process over the lecturer as it is required to follow the performance of each student and correct the mistakes that accompany learning, especially the first stage students, and therefore the teacher needs more time and effort to enrich the educational process and access to good and ideal performance for skill To be learned. The research sample included the first stage students in the Department of Physical Education and Sports Science who were (40) students and they were divided into two experimental groups and each group (20) students, and the experimental approach was used, and the researcher applied the research experience to the experimental group and through the results it has The researcher concluded that the exercises above learning were the best in learning the motor sentences in the technical gymnastics, and in statistical significance. The researcher recommended the need to emphasize the use of exercises above learning by the teachers of gymnastics in learning the skills of gymnastics.